The Effect of Performance Accountability and Internal Control on Good Governance, Supply Chain Governance and its Impact on Government Performance - Mulyasa, E; Mulyasana, Dedi; Anwar, Harry; Kurniadi, Budi (ExcelingTech, 2020)
The government's performance in carrying out good governance is a prerequisite for realizing the aspirations of society and achieving the ideals of the nation and state. This study analyzes the effect of Accountability and Internal Control on Good Governance, and supply chain governance, and its impact on government performance. This study uses an ex post facto quantitative approach, with survey methods and correlational designs. The data collected is quantitative primary data in associative form supported by secondary data. Data instruments for this study were questionnaires which were evaluated for their validity and reliability prior to further analysis. Data evaluation was performed using SPSS 22 for Windows. The results showed that the variables of performance accountability and internal control had a positive and significant effect on good governance and supply chain governace and had a positive and significant impact on government performance, either directly or indirectly, either separately or simultaneously. Therefore it is recommended to the government to build good performance through the implementation of good governance, by paying attention to accountability and internal control in an integrated and sustainable manner.